Identification of the Formation of Character Education Values for Preschool Children in the Disruption Era - Nazarullail, Fikri; Maskulin, Dewi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – This study aims to identify character building for preschool-aged children in the era of disruption. This research produces percentages regarding applying the four character values: honesty, discipline, tolerance and independence.Design/methods/approach – This study uses a quantitative research method with a descriptive type. In this research, researchers conducted data mining using research instruments distributed online to students’ parents. The results of the analysis of the questionnaire that has been distributed to the parents of the students will later become quantitative data to determine the character development of students while at home.Findings – The results showed that parents’ formation of character values for pre-school-aged children obtained data as many as 365 (95.05%) parents always familiarize and apply the value of honesty. 263 (64.49%) parents always familiarize themselves and apply the value of discipline. 214 (55.73%) parents always get used to and apply the value of tolerance, and as many as 272 (70.83%) parents always get used to and apply the value of independence.Research implications/limitations – The research focus on the four character values is based on the results of previous research, which the researchers used as a reference because students in the early age category are still in the process of growth and development, so the internalization of the eighteen character pillars has not been fully formed.Practical implications – These four character values have different scores where the student’s parents prioritize instilling the values of honesty in educating their children in the family environment. The lowest score results indicate that tolerance is a character education value not applied to the early childhood category. The researcher hopes there will be a similar type of research to analyze the application of tolerance character values in the elementary and middle school age categories.Originality/value – The significance of this research that has been carried out is to see the role of parents in implementing character education values in the family environment. It is hoped that future research can link the four character values to correlational research.Paper type: Case study